2016
DOI: 10.1038/srep37975
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Membrane-Associated Proteins of Exosomes Released from Human Macrophages after Mycobacterium tuberculosis Infection

Abstract: Tuberculosis (TB) is the deadliest infectious disease worldwide. One obstacle hindering the elimination of TB is our lack of understanding of host-pathogen interactions. Exosomes, naturally loaded with microbial molecules, are circulating markers of TB. Changes in the host protein composition of exosomes from Mycobacterium tuberculosis (Mtb)-infected cells have not been described, can contribute to our understanding of the disease process, and serve as a direct source of biomarkers or as capture targets to enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 34 publications
(46 reference statements)
0
50
0
3
Order By: Relevance
“…Upregulation of SYWC in the host leads to restriction of free tryptophan, and tryptophan depletion is lethal to M. tuberculosis ( 35 ). SYWC has very recently been found upregulated in human THP-1 cells infected with M. tuberculosis ( 36 ). In a separate mechanism during TB infection, tryptophan often becomes limiting due to its conversion to kynurenine by indoleamine 2,3-dioxygenase ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of SYWC in the host leads to restriction of free tryptophan, and tryptophan depletion is lethal to M. tuberculosis ( 35 ). SYWC has very recently been found upregulated in human THP-1 cells infected with M. tuberculosis ( 36 ). In a separate mechanism during TB infection, tryptophan often becomes limiting due to its conversion to kynurenine by indoleamine 2,3-dioxygenase ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has indicated that exosomes and their cargo can be transferred from one cell to another, resulting in the cell-to-cell communication via various functional biomolecules including proteins, bioactive lipids, and RNA, which can alter recipient cell functions. [23][24][25] For instance, exosome-like vesicles from T. gondii-infected HFF cells could attach and deliver their contents to uninfected cells, thereby leading to altered functions in the uninfected cell. 20 In addition, exosomes secreted by T. gondii-infected L6 cells could change the host cell proliferation and alter the host cell cycle.…”
mentioning
confidence: 99%
“…Extracellular vesicles are involved in immune activation and antigen presentation during Mycobacterium tuberculosis infection. M. tuberculosis manipulates the secretion of extracellular vesicles in mammalian cells by increasing the abundance of immune-related proteins (Diaz et al, 2016), and packaging bacterial molecules within host-derived exosomes (Giri et al, 2010;Kruh-Garcia et al, 2014). M. tuberculosis proteins within these exosomes activate the host immune response in the recipient cell (Giri et al, 2010) ( Fig.…”
Section: Immune Activationmentioning
confidence: 99%